Workshop Penyusunan Bahan Ajar Outdoor Matematika Berbasis Lokal Konteks untuk Guru Sekolah Dasar - Agus Susanta; Irwan Koto; Edi Susanto (Forum Kerjasama Pendidikan Tinggi, 2023)
The implementation of the independent learning curriculum in Indonesia is the government's effort to improve the quality of education. However, the crucial problem is the limited learning resources in schools relevant to curriculum requirements. So, teachers must be innovative in preparing resources for classroom learning by referring to the curriculum, one of which is using relevant context. This activity aims to provide teachers with insight and experience in preparing outdoor mathematics teaching materials based on local context. Partners in this activity are elementary school teacher working groups (KKG) in Kepahiang Regency. The method used in this activity is a training method through coercion. The activity stages consist of (1) the activity preparation stage, (2) the coordination and socialization stage, (3) the workshop stage, (4) the assignment and evaluation stage, and (5) the product distribution stage in the form of teaching materials. This activity was attended by 33 elementary school teachers in Kepahiang Regency. The results of this service activity are: (1) an increase in teacher understanding in preparing outdoor mathematics teaching materials based on local context, (2) increased motivation of participants in designing outdoor mathematics teaching materials based on local context, (3) the preparation of outdoor mathematics teaching materials for elementary school students in the Kepahiang context. The suggestion from this service activity is that teachers should be able to be innovative in building open materials using contexts that are familiar and close to students.